Pengembangan Media Pembelajaran Fiberglass Simulator Pernapasan Manusia Di Kelas V UPT SDN 17 Gresik - Imroah Lailatuz Zaikiyah (Lembaga Pengembangan Kinerja Dosen, 2023)
The main objective of this research is to study learning media Fingerglass human breathing simulator. Utilization of simulation models designed to resemble the human respiratory system serves as an invaluable educational tool. The aim is to facilitate a comprehensive understanding of scientific concepts, particularly in the field of natural sciences, with the ultimate goal of practical application in everyday life. By using this simulator it is hoped that students will be involved to be actively involved in the learning process, fostering a high interest in understanding the subject matter. This research took place at UPT SDN 17 Gresik for Grade 5 students. The model used is a simulator of the human respiratory system following the ADDIE model, which consists of five stages: analysis, design, development, implementation and evaluation. This model is based on the scientific approach to ADDIE development theory outlined by Robert Maribe Branch. The validation process for two levels of material expert validators I and II resulted in a validation level of 85% indicating that the material was included in the valid category. Likewise, the results of the validator material expert validator II show a validation level of 100% which is also included in the valid category. This implies that the contents of the learning media are relevant to the subject matter of the fifth grade Human Respiratory System in elementary school. Thus it can be concluded that the quality of the Fiberglass Learning Media Human Breathing Simulator meets valid criteria in terms of the material it contains. In addition, the student's response obtained a value of 87% indicating that the Human Breathing Simulator Fiberglass Learning Media was very suitable for use in the learning process